Sequencing and analyses of all known human rhinovirus genomes reveal structure and evolution - Palmenberg, A.C.; Spiro, D.; Kuzmickas, R.; Wang, S.; Djikeng, Appolinaire; Rathe, J.A.; Fraser-Liggett, C.M.; Liggett, S.B. (American Association for the Advancement of Science, 2009)
Infection by human rhinovirus (HRV) is a major cause of upper and lower respiratory tract disease worldwide and displays considerable phenotypic variation. We examined diversity by completing the genome sequences for all known serotypes (n = 99). Superimposition of capsid crystal structure and optimal-energy RNA configurations established alignments and phylogeny. These revealed conserved motifs; clade-specific diversity, including a potential newly identified species (HRV-D); mutations in field isolates; and recombination. In analogy with poliovirus, a hypervariable 5? untranslated region tract may affect virulence. A configuration consistent with nonscanning internal ribosome entry was found in all HRVs and may account for rapid translation. The data density from complete sequences of the reference HRVs provided high resolution for this degree of modeling and serves as a platform for full genome-based epidemiologic studies and antiviral or vaccine development.